Hadith #4341 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hilal bin Khbab هلال بن خباب; Ikrama عكرمة; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
I asked AbuTha’labah al-Khushani: What is your opinion about the verse “Care for yourselves”. He said: I swear by Allah, I asked the one who was well informed about it; I asked the Messenger of Allah (ﷺ) about it. He said: No, enjoin one another to do what is good and forbid one another to do what is evil. But when you see niggardliness being obeyed, passion being followed, worldly interests being preferred, everyone being charmed with his opinion, then care for yourself, and leave alone
Grade: Hasan